REPRODUCTIVE BIOLOGY OF Moolgarda sp. IN SEGARA ANAKAN LAGOON CILACAP DISTRICT, CENTRAL JAVA - Julia Syahriani Hasibuan; Sulistiono Sulistiono (Journal of Aquaculture Development and Environment, 2020)
Segara Anakan lagoon was water located in the estuary between Ciamis regency and Cilacap regency. The purpose of this research is to observe sex ratio, the maturity level of gonad, and the gonad maturity index of Moolgarda sp. Sampling was conducted for three months, from March to May 2017. The method used is a simple random sampling method. The results of research that the sex ratio of Moolgarda sp. male is higher than female. The gonad maturity level of Moolgarda sp. was obtained from levels I, II, III, and IV. The Gonad Maturity Index value Moolgarda sp. males ranged from 0.0022% - 1.3041% while GMI Moolgarda sp. female 0.0424% - 5.5827% with a fecundity of Moolgarda sp. from 7356 - 131350 eggs.